A presença da ordem dos frades menores capuchinhos em Mato Grosso (1954-1964) - Silva Neto, Rafael José Da (2024)
This study aims to examine the involvement of the Capuchin Friars Minor in Mato Grosso, where they assumed various parishes in the dioceses of Corumbá and Campo Grande. The period covered by the work includes the expansion of the Province of Caxias do Sul towards the Northwest of São Paulo in 1946, followed by migration to Mato Grosso in 1954, and includes the initiation of the expansion to Goiás and the Federal District in 1958. The institutional interests that motivated these migrations will be explored, both within the internal context of the religious order and from the perspectives of the diocesan bishops. Additionally, the challenges and difficulties faced by the friars during this process of territorial expansion will be examined. The research will also investigate the relationships established with the ecclesiastical hierarchy and local populations, as well as pastoral work in the parishes and the strategies adopted to manage the parishes and reform Catholicism. The sources used include the "livros tombo" (church records) and parish registers of the parishes where the friars worked, as well as correspondence exchanged between the friars and internal circulation periodicals of the Order. The theoretical framework is based on various Cultural History bibliographies, highlighting Foucault and his concept of governmentality to analyze the functioning of power and governance exercised by the friars in their initial parishes in Mato Grosso. This dissertation provides an overview of the presence, establishment, and pastoral work of the first Capuchin Friars Minor in Mato Grosso from 1954 to 1964, surpassing memorialist discourses that praised the Order's presence in the region in a factual and celebratory manner. The migration of the Capuchin order was accompanied by material and adaptation difficulties; however, the friars sought to establish themselves by nurturing close relationships with the political and economic elites of Mato Grosso, exercising their power and influence, gradually ensuring their integration into Mato Grosso society.